Production, optimization, characterization, and application of chitinase from Bacillus proteolyticus isolated from the rhizosphere of diseased arecanut palm - M. Jeeva; K. U. Minchitha; S. Swetha (Brazilian Journal of Microbiology, 2026)

Stress-mediated root microbiome shifts and the ‘cry for help’ response in banana (Musa spp.) - V. Swetha; M. Kavino; S. Nakkeeran; S. Marimuthu; R. Raghu (Physiological and Molecular Plant Pathology, 2026)

Exploring Bacteriocin from Lactobacillus crispatus for Sustainable Bio-Preservation of Sprouts - Kavyarathna; Minchitha K U; Nagananda G S; Sandeep Suryan; Swetha S (Next Research, 2026)

Talaromyces atroroseus pigment-derived silver nanoparticles functionalized with 6-benzylaminopurine for enhanced in vitro growth of Musa acuminata cv. ‘Grand Nain’ - Kavyarathna; R. Aakash; M. Nithin Kumar; K.U. Minchitha; S. Swetha; Sandeep Suryan; G.S. Nagananda (Biocatalysis and Agricultural Biotechnology, 2026)

Emerging contaminants in urban Soils: Characterization, sources, and environmental impacts of microplastics in southern India - M. Bhuvaneswari; V. Gopal; R. Vinoth; R. Aakash; N.M. Swetha; S. Vinoth kumar; R.R. Krishnamurthy; M.Suresh Gandhi; Renuka Sharma; Ramamoorthy Ayyamperumal (Physics and Chemistry of the Earth, Parts A/B/C, 2025)

Frequency of γ-H2AX foci, micronucleus formation, and radiation dose to the blood lymphocytes in pediatric and adult participants underwent computed tomography imaging - Divya K. Mohan; Nandhini K.; Aishwarya S.; Senthil Kumar M.; Swetha K.; Akshaya J.; Sudha Pattan; Venkata Sai P.M.; Venkateswarlu Raavi; Venkatachalam Perumal (Mutation Research - Genetic Toxicology and Environmental Mutagenesis, 2025)

Synergistic Use of Scatterometer and Ocean Colour Monitor Onboard EOS-06 Satellite for Various Oceanographic Applications - Neeraj Agarwal; Jishad M; Jai Kumar; Sanjiba Kumar Baliarsingh; Naga Swetha; Smitha Ratheesh; Suchandra Aich Bhowmick; Ratheesh Ramakrishnan; Abhisek Chakraborty; Rajesh Shikakoli; Manche Shiva Shankar; Reema Mathew; et al. (Journal of the Indian Society of Remote Sensing, 2025)

Long-term trends in heavy metal contamination of marine sediments in the Arabian Gulf: A meta-analysis - S. Swetha; S. Veerasingam; S. Rajendran; Hassan Hassan; Muhammad Zia U. R. Rahman Hashmi; Hamood Alsaadi; Nelson Rangel-Buitrago; Fadhil N. Sadooni (Environmental Monitoring and Assessment, 2025)
Heavy metal (HM) contamination in marine sediments is a critical environmental concern due to its potential ecological and human health impacts. This study provides a comprehensive assessment of the spatial and temporal evolution of HM contamination in Arabian Gulf sediments over a 33-year period (1991–2024). Contamination levels were evaluated using key sediment quality indices such as the contamination factor (CF), geoaccumulation index (I g ₑₒ), pollution load index (PLI), and ecological risk index (ERI) based on available meta-data. Spatial analysis revealed that marine sediments along the Iranian and Saudi Arabian coasts exhibited higher contamination levels compared to those of other Gulf countries. This elevated contamination is likely attributed to industrial discharges, oil spills and effluent releases from desalination plants. Arsenic (As), cadmium (Cd), copper (Cu), nickel (Ni), and lead (Pb) emerged as the primary toxic contributors to sediment pollution. Overall, HM contamination status in the region is predominantly low to moderate, with localized hotspots near industrialized coastal zones. The study highlights the need for scientifically informed waste management strategies to mitigate HM contamination, particularly in nearshore environments impacted by industrial activities. Furthermore, it recommends the implementation of continuous monitoring programs to track temporal trends and identify emerging contamination sources. These findings provide critical insights for environmental managers and policymakers in developing sustainable pollution mitigation frameworks and enhancing the resilience of marine ecosystems in the Arabian Gulf.

Ingestion of weathered high density polyethylene microplastics-induced oxidative stress and modulation of antioxidant responses in post larval stages of Litopenaeus vannamei - M. Leela; V. Pushpalatha; S. Swetha; S. Anusuya; S. Madhavan; S. Eswari; H. Thilagam; R. Thiagarajan; R. Krishnamurthy (Frontiers in Marine Science, 2025)

Influence of large-scale climate modes (ENSO, IOD and PJ) on marine heatwave characteristics in the Indian ocean region - S. Swetha; K. V. Ramesh; V. Rakesh (Theoretical and Applied Climatology, 2025)

Climate Geoscience–Based Disaster Management in Healthcare Analysis by Markov Q-Transfer Adversarial with Cloud Computing - Jhade Srinivas; B. Rebecca; Kovvuri N Bhargavi; Velma Reddy Swetha; S. Spandana; Divya Priya Degala (Remote Sensing in Earth Systems Sciences, 2025)

Quantifying CMIP6 models’ performance in simulating marine heatwaves over the Indian Ocean region: A comprehensive analysis of key MHW properties and future projections - S Swetha; K V Ramesh (Journal of Earth System Science, 2025)

Fusion of MobileNet and GRU: Enhancing Remote Sensing Applications for Sustainable Agriculture and Food Security - Ushus. S. Kumar; B. Suresh Chander Kapali; A. Nageswaran; K. Umapathy; Pradeep Jangir; K. Swetha; M. Amina Begum (Remote Sensing in Earth Systems Sciences, 2025)

Integrating nanomaterials and plant growth-promoting rhizobacteria for enhanced plant disease management: an overview - S. Swetha; M. Jeeva; K. U. Minchitha (Journal of Plant Diseases and Protection, 2025)

Sulfur vacancies engineered self-supported CdCr2S4 as cascade nanoreactor for efficient photocatalytic degradation of rifampicin - S. Sudheer Khan; J.P. Steffy; S. Swetha; Asad Syed; Abdallah M. Elgorban; Alanoud T. Alfagham; Meenakshi Verma; Ling Shing Wong (Journal of Water Process Engineering, 2025)

Strategically tailored double S-scheme heterojunction in h-MoO3 doped Bi7O9I3 decorated with Cr–CdS quantum dots for efficient photocatalytic degradation of phenolics - S. Swetha; Tahani Awad Alahmadi; Mohammad Javed Ansari; S. Sudheer Khan (Journal of Cleaner Production, 2024)

Triple-mechanism driven Fe-doped n-n hetero-architecture of Pr6O11-MoO3 decorated g-C3N4 for doxycycline degradation and bacterial photoinactivation - S. Swetha; Mostafa A. Abdel-Maksoud; Mohammad K. Okla; B. Janani; Turki M. Dawoud; Mohamed A. El-Tayeb; S. Sudheer Khan (Chemical Engineering Journal, 2023)

Black carbon over tropical Indian coast during the COVID-19 lockdown: inconspicuous role of coastal meteorology - Aditya Vaishya; Subha S. Raj; Aishwarya Singh; Swetha Sivakumar; Narendra Ojha; Som Kumar Sharma; Raghunathan Ravikrishna; Sachin S. Gunthe (Environmental Science and Pollution Research, 2023)

A Comparative Evaluation of Four Different Immunoassays in the Diagnosis of Cystic Echinococcosis Using a Crude and Purified Hydatid Cyst Fluid Antigen - P. Vinayaka Siddartha; A. Jagadeesh Babu; T. Madhava Rao; V. Chengalva Rayulu; C. S. Swetha (Acta Parasitologica, 2022)

Rothia santali sp. nov., endophytic bacteria isolated from sandalwood (Santalum album L.) seedling - Ngangyola Tuikhar; Kiran Kirdat; Gayatri Nair; S. Padma; Vipool Thorat; P. Swetha; Shivaji Sathe; R. Sundararaj; Amit Yadav (Archives of Microbiology, 2022)

Decadal prediction skill for spring and summer surface air-temperature over India and its association with SST patterns in CFSv2 and CNRM coupled models - S Swetha; Jasti S Chowdary; Anant Parekh; C Gnanaseelan (Journal of Earth System Science, 2021)

Mitigation of Drought Stress by Piriformospora indica in Solanum melongena L. cultivars - S. Swetha; T. Padmavathi (Proceedings of the National Academy of Sciences, India Section B: Biological Sciences, 2020)

Treatment of fluoride-contaminated water. A review - P. Senthil Kumar; S. Suganya; S. Srinivas; S. Priyadharshini; M. Karthika; R. Karishma Sri; V. Swetha; Mu. Naushad; Eric Lichtfouse (Environmental Chemistry Letters, 2019)

Aseptic Culture Establishment Using Antibiotics with Reference to Their Efficiency and Phytotoxicity in Difficult-to-Establish Native Ney Poovan Banana (Musa, AB) - Pooja Bohra; Ajit Arun Waman; B. N. Sathyanarayana; K. Umesha; S. R. Anu; H. G. Swetha; R. K. Gourish (Proceedings of the National Academy of Sciences, India Section B: Biological Sciences, 2014)

The 18S rDNA gene discriminates between red-listed and unexplored ethnomedicinal species of Myristicaceae restricted to humid tropics of India - T. E. Sheeja; O. B. Rosana; V. P. Swetha; R. S. Shalini; S. Siju; R. Dhanya; P. R. Rahul; B. Krishnamoorthy (Genetic Resources and Crop Evolution, 2014)